Guerrillas and terrorists - Clutterbuck, Richard L. (Ohio University Press, 1980)
Terrorism and guerrilla warfare, whether justified as resistance to oppression or condemned as disrupting the rule of law, are as old as civilization itself. The power of the terrorist, however, has been magnified by modern weapons, including television, which he has learned to exploit. To protect itself, society must understand the terrorist and what he is trying to do; thus Dr. Clutterbuck's purpose in writing this book: "to contribute to the understanding and cooperation between the police, the public and the media."